2016
DOI: 10.1016/j.jped.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Infant feeding: beyond the nutritional aspects

Abstract: Responsive feeding is very important in dietary habit formation and should be encouraged by health professionals in their advice to families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
21

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 38 publications
0
50
0
21
Order By: Relevance
“…Given its relevance, the impact of maternal ED on children's feeding and mealtimes is an area that has received considerable attention. Feeding the infant is a crucial task of parenting not only because it can absorb considerable part of the day in the early stages of life but also because it is one of the most important means of communication between mother and child (Silva et al 2016).…”
Section: Study Resultsmentioning
confidence: 99%
“…Given its relevance, the impact of maternal ED on children's feeding and mealtimes is an area that has received considerable attention. Feeding the infant is a crucial task of parenting not only because it can absorb considerable part of the day in the early stages of life but also because it is one of the most important means of communication between mother and child (Silva et al 2016).…”
Section: Study Resultsmentioning
confidence: 99%
“…A study on infant feeding conducted by Goes et al 23 in Lisbon, Portugal, reported greater involvement of mothers (93.1%) compared to fathers (6.9%). According to Silva, Costa, and Giugliani, 24 the interaction with the person who feeds the child determines if the feeding will be responsive or not and will influence the child's eating habits and relationship with food. Other studies carried out in Brazil report that help from a relative at home increases the risk of interrupting breastfeeding before the infant reaches four months of age.…”
Section: Discussionmentioning
confidence: 99%
“…The literature demonstrates the pertinence of the learning process in the formation of feeding behaviors, and that stimuli can last throughout childhood/adolescence and even into adulthood. 31 , 32 , 33 Furthermore, there is a positive relationship between eating with the family and interacting with family members. 33 Thus, the presence of the child in the same environment as the rest of the family while they are eating meals - in conjunction with healthy foods - is of great importance in aiding the implantation/continuation of the method.…”
Section: Discussionmentioning
confidence: 99%